Theoretical Study of Negative Material Bias Index Symptoms - Simbolon, Tuaraja (Talenta Publisher, 2020)
Theoretical research on the phenomenon of negative refractive index materialwas cunducted. The material is a known metamaterial that can manipulate electromagneticwaves through it. By changing the permeability and permittivity of a medium that is worthimaginary, then the value is included in the equation will produce a refractive index that isnegative. This value can be achieved through material forms are designed so that themagnetic field and electric field manipulation. The equation used on electromagnetic wavesthat Maxwell's equations, is revealed to be some similarities propagation magnetic field andelectric field. The Methods Finite Difference Time Domain (FDT D) as a modifier equationwas then equations analysis, simulated using MatlabR2014 program. Based on simulationresults, visible when the electromagnetic waves through a material metamaterial, the wavesare deflected, do not pass part of the material covered.